Epitaxy of GaN Film by Hydrogen Plasma Assisted MOCVD - Sugianto Sugianto; A. Subagio; Erzam Erzam; R.A. Sani; M. Budiman; P. Arifin; M. Barmawi (Institute for Research and Community Services (LPPM) ITB, 2001)
Abstract. We have studied the effect of hydrogen plasma on GaN film, grown by plasma-assisted metalorganic chemical vapor deposition (MOCVD). GaN films grown on a sapphire (0001) without the buffer layer have a polycrystalline structure. While films grown using the buffer layer tends to have a single crystal orientation. We have tried to increase the growth rate by varying the TMGa:N ratio. We found that the growth rate of the films were 450 nm/h with TMGa:N ratio of 1:600. However the films show a polycrystalline structure. Using hydrogen plasma during the growth, we have shown by XRD analysis that the films structure was highly oriented in (0002) plane parallel to substrate and the crystalline quality is improved. Epitaksi Film GaN dengan MOCVD Berbatuan Plasma HidrogenSari. Telah dipelajari efek dari plasma hydrogen pada film Gan, yang ditumbuhkan dengan MOCVD yang dibantu dengan plasma. Film GaN ditumbuhkan di atas safir (0001) tanpa bantuan lapisan penyangga mempunyai struktur polikristalin. Sedangkan film yang ditumbuhkan dengan bantuan lapisan penyangga mempunyai kecenderungan membentuk Kristal dengan orientasi tunggal. Telah dicoba untuk menaikkan kecepatan pertumbuhan Kristal dengan mengubah-ubah perbandingan TMGa:N. Telah diperoleh kecepatan pertumbuhannya menjadi 450nm/jam bila perbandingan tersebut 1:600, akan tetapi strukturnya memperlihatkan sifat polikristal. Dengan bantuan plasma hidrogen analisis XRD menunjukkan bahwa orientasi film sejajar dengan arah (0002) dan sifat kristalnya dapat diperbaiki.